Lactate in cerebrospinal fluid as an early marker of post-neurosurgical bacterial meningitis: establishing a novel cut-off value and literature review - Fochi, Antonella; Gómez, María Eugenia; Jacobsen, Darío; Fernández Machulsky, Nahuel; Minghinelli, Federico Eduardo; Perazzi, Beatriz (Revista Argentina de Neurocirugía, 2024)
Background: post-neurosurgical bacterial meningitis (PNBM) has a high mortality rate. Rapid diagnosis is essential. The gold standard is cerebrospinal fluid (CSF) culture, but it takes time, and unnecessary empirical antibiotics are used. It is important to evaluate other parameters that facilitate early detection.Objectives: to assess the utility of CSF lactate as an early marker of PNBM, to establish its cut-off point in our population, and to correlate lactate levels with protein and cells/mm3.Methods: retrospective study. Lactate, protein, cells, glycorrhachia, and culture were studied. Categorization into three groups: confirmed PNBM (C), presumptive PNBM (P), and negative PNBM (N). The Mann-Whitney test was used to compare medians. We grouped PNBM C with PNBM P and performed ROC curves to determine the cut-off point. For the correlation analysis, we calculated the Spearman coefficient between lactate versus cells/mm3 and lactate versus proteinorrachia.Results: we observed a significant difference in the median lactate of PNBM C and PNBM P compared to PNBM N. This was not the case between PNBM C and PNBM P. The area under the ROC curve was: 0.901. The highest cut-off point for lactate in this context was 4.85 mmol/L, with sensitivity: 76.9% and specificity: 95%. Lactate correlated positively with cells/mm3 and proteinorrachia.Conclusion: a new cut-off point for CSF lactate of 4.85 mmol/L was established for the early diagnosis of PNBM. Additionally, the correlation analysis of lactate with cell counts and proteinorrachia was positive and statistically significant for PNBM.
Keywords: Bacterial meningitis; Cerebrospinal fluid; Lactate; Post-neurosurgical meningitis